ANALISIS POSTUR KERJA PADA PEKERJAAN PENGELASAN DI PT. XYZ (PERSERO) PADA PROYEK PEMBANGUNAN JETTY PLTMGU LOMBOK PEAKER DENGAN MENGGUNAKAN REBA, NBM DAN TREE DIAGRAM - Nurulinzany; Iksan Adiasa; Puput Sri Utami (Hexagon, 2025)
XYZ is a State-Owned Enterprise (BUMN) engaged in the construction sector. One of the infrastructures currently being built by PT. XYZ is the Construction of the Lombok Peaker PLTMGU Jetty in Mataram. Based on the results of observations, it was found that there was a risk of danger to welding workers that could cause work-related illnesses in spun pile welding workers or piles, so further analysis is needed. This study aims to analyze work postures and complaints and provide suggestions for welding work at PT. XYZ on the Lombok Peaker PLTMGU jetty construction project. The methods used are the Rapid Entire Body Assessment (REBA), Nordic Body Map (NBM) and tree diagram methods. The results of the study obtained REBA on the first, second and fourth welders were at a high risk level. The results of the Nordic body map score for welder 1 are in the moderate category, meaning that corrective action may be needed. Several workers filled out complaints of pain in several parts of the body. The proposed improvements are adequate rest, adjusting the height of the pile to be welded to the height of the welder, the welder welding with a more upright body, and providing a chair for the welder. It is expected that this research can minimize the risk of work-related illness in welding work at PT. XYZ on the Lombok Peaker PLTMGU jetty construction project.